Effect of Titanium Dioxide Nanoparticles on in Vitro Fertilizing Potential in Albino Mice - Ramin Jahangirfard (Fasa University of Medical Sciences, 2020)
Background & Objectives: Toxic free radicals produced by titanium dioxide nanoparticles have adverse effects on the reproductive system and can affect the semen quality and decrease fertility. The purpose of this study was to assess the effect of titanium dioxide on in vitro fertilizing potential in albino mice. Materials & Methods: In this experimental study, 24 adult male mice were divided into 4 control and experimental groups. The experimental groups received titanium dioxide at 2.5, 5 and 10 mg/kg by gavage. After the end of the treatment period, animals were sacrificed by cervical dislocation and then sperm samples were collected from cauda epididymis to investigate in vitro fertilization. The level of p<0.05 was considered significant. Results: In vitro fertilization results showed that titanium dioxide significantly reduced embryonic quality and stages of embryological development compared to the control animals. Also, the percentage of arrested embryos in the experimental groups was significantly enhanced versus the control (p<0.05). Conclusion: The present results exhibited that oxidative stress produced by titanium dioxide causes sperm quality decline and decrease in vitro fertilizing potential in a dose-dependent manner.